Characterisation of Kenana cattle at Um Banein, Sudan - Saeed, A.M.; Ward, P.N.; Durkin, J.W.; Wilson, R.T.; Light, D.E. (International Livestock Centre for Africa, 1987)
Results of a study carried on the reproductive performance, herd management, weight & growth, milk production & mortality of Kenana cattle at Um Banein Livestock Research Station (Sudan).